ANALISIS TINGKAT KEPUASAN KONSUMEN TERHADAP PELAYANAN BONGKAR-MUAT BARANG PADA TERMINAL PETIKEMAS SEMARANG - Handajani, Mudjiastuti; Janto, Yoeli (FSTPT Indonesia, 2015)
This study aims to analyze the level of consumer expectations and service performance and user satisfaction level loading service at Semarang Container Terminal. It also analyzes the factors that must be maintained, high priority, low priority and customer satisfaction. Total samples are 73 respondents (companies) with data analysis using Important Performance Analysis.Based on the analysis Cartesian diagram is known that factors are considered important in accordance with the reality perceived customer so there is relatively high level of satisfaction on factors Clarity Services, Disciplinary Service Officer, Justice of service and comfort environment. While the factors are considered less important by customer and in fact not too special in which an increase in attributes in this quadrant can be reconsidered due to influence on perceived benefits by small customer are factor procedures, responsibilities, speed of service and courtesy and hospitality workers.